A Proposed PPST aligned capability enhancement program for public junior high school teachers - Venterez, Jr., Leopoldo P. (University of Pangasinan : [s.n.], 2020)
Over the past two decades, policymakers have called for improvements in the academic performance of Filipino students. Many educational reformers, particularly those associated with the standards movement, hold that the key to improving student performance les in improving schools, teachers teaching proficiency and students attitudes towards learning. This study aimed to survey and describes the level of teaching proficiency of the junior high school teachers in Calasiao Districts for the School rear 20l9 - 2020. The study focused on assessing the Teacher's Proficiency Level along with the / domains of PPSI as perceived by themselves and their School leads. The researcher employed a descriptive-developmental method of research. The study targeted two hundred eleven (211) junior high school teachers and four (4) School Heads in 4 different secondary high Schools in Calasiao, Pangasinan. the researcher found out that as overall level of proficiency of the junior high school teachers across the seven domain of PPST was (3z(BAdvanced" as perceived both by the teachers and the targeted school heads. It was also found out that the educational attainment of the teachers plays a very significant role in their level of proficiency. Based on the findings of the study, the researcher came up with a proposed capability enhancement program and its acceptability was assessed by the teachers and the school heads. It was found out that the said proposed capability enhancement program was acceptable with an overall weighted mean of 4.44. Thus, it is recommended that the proposed capability program to enhance the proficiency level of the junior high school teachers should be adopted to continuously improve the teachers' competency and proficiency across the seven domains of PPST (Philippine Professional Standards for Teachers).s
Bibliography: pages 109-113.
CHED-La Union
Keywords: Teachers -- Public schools